Comparação do transtorno de ansiedade generalizada, consumo alimentar e estado nutricional entre discentes matriculados em períodos finais e iniciais de cursos da área da saúde de uma universidade de Belém, Pará - MARTINS, Marcus Thadeu Diniz (2023)
The aim of this study was to compare behavioral parameters, generalized anxiety disorder, nutritional status and food intake among beginning and almost ending health graduation courses at a university in Belém, Pará, Brazil. This is a crosssectional study with convenience nonprobabilistic sampling of students, of both sexes, entering and almost graduating from all courses in the field of health at the Federal University of Pará, willing to answer the survey's online questionnaire. Social, economic, demographic aspects, as well as body mass index, smoking, consumption of alcoholic beverages, physical activity, food intake and generalized anxiety disorder were evaluated, among those entering and almost graduating from undergraduate health courses. Descriptive statistics of the data were performed, as well as the Chisquare, MannWhitney tests and binary logistic regression analysis, all with alpha at 5%. Was found that almost graduated students were 6.3 times more likely to consume alcoholic beverages (p = 0.000), and 1.3 times more likely to eat ultraprocessed foods (p = 0.047) than those entering undergraduate courses. For the other variables, there was no statistically significant difference. Therefore, it can be seen that students who almost completed health courses were more likely to consume alcoholic beverages and ultraprocessed foods, compared to newcomers.